Income Disparity between Legislative Institutions and the General Public in Relation to Social Welfare Aspects: A Comparative Study of Indonesia and Malaysia - Relys Sandi Ariani; Arini Zulfaida; Fidela Dzatadini Wahyudi (Institut Agama Islam Negeri Curup, 2025)
Pancasila, as the foundation of the Indonesian state, upholds social justice for the people with the aim of equality in all areas, especially public income. However, recent research has found that the income gap between the Indonesian Legislative Institution and the Indonesian public is significantly different from that in Malaysia. This can certainly affect the welfare of the people of those countries. Therefore, the author analyzes and examines in more depth the income gap between the Legislative Institution and the public in Indonesia and Malaysia related to public welfare. This study uses a normative legal research type with a statutory and comparative approach, data sources are primary legal materials and secondary legal materials from books, journals, and legal dictionaries. The income gap between the legislative institution and the public in Indonesia reaches 10x-14x, while in Malaysia it is 4x-5x. This gap creates social injustice and hinders public welfare. Therefore, the values ​​of social justice in Pancasila do not function well in practice. It is necessary to strengthen Pancasila from an early age in shaping the character of the Indonesian people.Civic Awareness and Social Justice.